The effects of carriers and metal complexes of thermal and storage of encapsulated red cabbage extract. - Jakaphan Ratanapoompinyo; Nguyen, Loc Thai; Athapol Noomhorm; Anal, Anil Kumar; RTG Fellowship; Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2015)
Red cabbage contains a rich source of anthocyanins which can be used as natural food colorants. However, anthocyanins are sensitive to environmental factors such as pH, temperat ure, enzymes, oxygen and light. Metal ions, through complexation with anthocyanins, have been extensively used to produce desired color or stabilize color of anthocyanins in plant extract. So far, scarce information is available on the effects of metal ions on the stability and character istics color of anthocyanins under food processing conditions such as heat treatments, drying or storage. In this study, the effects of metal ions (Al 3+ ,Ca 2+ ,Fe 3+ and Sn 2+ ), popularly used metal - anthocyanin copigmentation, on the stability and characterist ic color of red cabbage anthocyanins during thermal treatment, spray drying and storage were investigated. Obtained results indicated that UV - Vis spectra of red cabbage anthocyanins exhibited significant changes in the presence of metal ions. The additio n of metal ions induced diverse effects on anthocyanin pigments such as increase (hyperchromic) or decrease (hypochromic) of absorbance; shift of n max to higher wavelength (bathochromic) or lower wavelength (hypsochromic). The apparent shift in wavelength and intensity of peak absorbance evidenced the complexation of anthocyanins and metal ions. As compared to the control sample, Fe 3+ caused the most change in n max , following by Ca 2+ , Al 3+ and Sn 2+ . The hyperchromic effects were found for all the studied anthocyanin - metal ion chelates, with the exception of Al 3+ . The highest increase in absorbance intensity was noted for Sn 2+ whereas Ca 2+ and Fe 3+ were associated with the lowest change. Red cabbage anthocyanins were apparen tly more susceptible to thermal damage with the addition of metal ions. Highest loss of anthocyanins was ascribed to Sn 2+ and Fe 3+ but the effects were less severe with Al 3+ and Ca 2+ . The wavelength shift (bathochromic and hypsochromic) induced by metal io ns was negligible (P = 0.973). The shift of wavelength was also not significant for different metal ions (P = 0.973). Al 3+ anthocyanins complex remained relatively stable a s compared to other metal ions. During spray drying, combined thermal and oxydation effects caused more damage to anthocyanins in with all of metal ions . The highest loss of was recorded when Ca 2+ and Sn 2+ was used as cofactor. Reduced loss of total phenolic compounds (TPC) was noted when metal ions were added to the extract. Little variations were observed with respect to effects between different metal ions. The addition of metal ions seemed to be detrimental to heat stability of anthocyanins an d beneficial for TPC retention. The storage test demonstrated that Sn 2+ severely affected stability of anthocyanins in encapsulated red cabbage extract. Sample fortified with Al 3+ had slightly higher stability whereas Ca 2+ and Fe 3+ had lower stability, as compared to control sample. Significant improvement in the stability of phenolic compounds with the highest impact induced by Ca 2+ and Fe 3+ , following by Sn 2+ and Al 3+ . After 5 weeks of storage at 37 o C, metal ions can help retain a pproximately 6% more TPC as compared to control sample. No change in lightness (P = 173) and no significant difference (P =127) was found between samples fortified with different metal ions over 5 weeks. Significant reduction in redness (a*) was noted when Sn 2+ was added to the extract. Yellow color was not significant for samples different metal ions added (P = 0.206).
A thesis submitted in partial fulfillment of the requirements for the Degree of Master of Science in Food Engineering and Bioprocess Technology, School of Environment, Resources and Development
Thesis (M. Sc.) - Asian Institute of Technology, 2015
Keywords: Bioactive compounds; Thermal analysis; Food -- Storage; Encapsulation